Non-syndromic oral clefts and risk of cancer: a systematic review - Daniela Araújo Veloso Popoff; Mateus Prates Coelho; Daniella Reis Barbosa Martelli; Rajiv Saini; Ricardo Della Coletta; Hercílio Martelli-Júnior (University Library System, University of Pittsburgh, 2013)
Objective: To discuss the risk of cancer among relatives of individuals with cleft lip and palate (CL/P), as well as the risk of CL/P among relatives of individuals with cancer, since studies published currently have suggested  an increased risk of cancer among relatives of cleft individuals. Design: A systematic literature review was carried out in accordance with the Cochrane Collaboration Group protocol, including literature search strategy, selection of papers through the inclusion and exclusion criteria, data extraction and quality assessment. PubMed, Scopus and ISI - Web of Science databases were systematically searched using the fallowing search strings: "cleft lip and palate" AND "cancer", "oral clefts" AND "cancer" and "orofacial clefts" AND "cancer". Results: From 653 studies accessed, 8 comprised the final sample: 6 investigating CL/P index cases and their family history of cancer and 2 investigating individuals with cancer and their family history for CL/P. The sample sizes were not homogeneous. Oral clefts, the type of cancer and the degree of kinship family were not categorized in all studies. Leukemia, breast cancer and colon cancer were the most cited types, even as first-and-second degree relatives. Conclusions: An increased risk of cancer among relatives of cleft individuals could not be entirely confirmed. However, studies with this specific purpose suggest that first-and-second degrees relatives of cleft individuals have some types of cancer more often than unexposed families, highlighting that future studies should expand their samples to investigate possible common molecular mechanisms that allow relating oral clefts and cancer.